8th international scientific conference on defensive technologies OTEH-2018 (proceedings review) - Pokorni, Slavko J. (Vojnotehnički glasnik / Military Technical Courier, 2018)
The article presents the basic information about the overal results, significance, international programme committee and working areas of the 8th International Scientific Conference on Defensive Technologies, OTEH 2018, in comparison with the previous seven conferencies. The number of sections, number of papers, number of authors/coauthors, number of sessions and number of members of the scientific committee are presented in the review. This year’s conference has had the smalest number of papers published so far.
Keywords: international conference; OTEH; military technology; review